Detection of St. Louis encephalitis virus antigen in mosquitoes by capture enzyme immunoassay. - Tsai, T F (1987)
Surveillance methods that measure St. Louis encephalitis (SLE) virus activity in nature may provide forewarning of its epidemic occurrence in humans. An antigen capture enzyme immunoassay was developed to detect SLE virus in infected mosquitoes. The assay detected purified SLE viral antigen at a concentration of 62 pg/0.1 ml when antigen was incubated overnight; 250 pg/0.1 ml was detected in a single-day assay (antigen incubated for 3 h). The assay detected 67.9 and 70.8% of laboratory-prepared pools of infected mosquitoes after 3 h and overnight incubation, respectively. The sensitivity of the procedure was 90.5% in identifying pools with infectious titers greater than dex 3.0. The specificity of the assay was controlled by retesting positive pools preincubated with SLE virus and normal antibodies, which led to a diminution of signal in the pools containing viral antigen. The procedure was suitably specific in discriminating between SLE and related flaviviruses, detecting only high infectious doses of heterologous antigens.